ASSESSING THE IMPACT OF MOBILE HEALTH APPLICATIONS ON PATIENT ENGAGEMENT AND PUBLIC HEALTH - Dr Ashwini L H; Dr Vinaykumar L H; Dr Hanumanaik L (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Mobile health (mHealth) applications are gaining an increasing adoption and there is a possibility for them to have a large effect on patient engagement and public health outcomes. The purpose of this research is to determine the effect of mHealth applications on patient adherence to health behavior, health literacy, disease management, and ultimately, on health outcomes. The paper examines the effectiveness of mHealth tools to improve health literacy, to promote patient engagement, and to further public health programs by means of user app usage data, survey, and demographic. The results indicate that mHealth applications improve patient engagement, with 78% of users reporting better adherence to health promoting behaviors (e.g., medication adherence and physical activity). In addition, 65% of participants reported increased health literacy and 60% used mHealth apps for preventive health purposes. The demographic analysis revealed that younger users used these applications more than older adults (85% for younger people vs. 45% use for older people). It also finds that mHealth applications can contribute to improved health outcomes for the public, as 40 per cent of users indicated that they had better disease management and greater health literacy. These results show the promise of mHealth applications to improve individual and population health. The observations from this study provide valuable information that healthcare providers and policymakers plan to use mHealth technologies in more effective healthcare delivery and public health strategies.